Les lieux de la culture: une théorie postcoloniale - Bhabha, Homi K.; Bouillot, Françoise (Petite biblio Payot, 2019)
Sommaire"Salué aussi bien par Edward Said que par Toni Morrison ou J.M. Coetzee, Homi K. Bhabha est l un des théoriciens les plus importants et les plus influents du postcolonialisme. S'appuyant sur la littérature, la philosophie, la psychanalyse et l'histoire, il invite notamment à repenser les questions très actuelles d'identité et d'appartenance nationales ; à dépasser, grâce au concept très fécond d'hybridité culturelle, la vision d'un monde dominé par l'opposition entre soi et l'autre ; à saisir comment, par le biais de l'imitation et de l'ambivalence, les colonisés introduisent chez leurs colonisateurs un sentiment d'angoisse qui les affaiblit considérablement ; ou encore, plus largement, à comprendre les liens qui existent entre colonialisme et globalisation." -- Résumé de l'éditeur.
Keywords: approches et analyses; arts; com5170; cours; discipline; har4600; histoire; histoire et politique; identités; philosophie; postcolonialisme; premier cycle; psychanalyse; sciences; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études littéraires

La colonialité du genre - Lugones, María (Les cahiers du CEDREF, 2019)
Keywords: approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; philosophie; pol4212; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; système colonial; systèmes d'oppressions; thématiques

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences